2019
DOI: 10.1089/vio.2018.0005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Psychological Consequences of Sexual Assault in Haiti

Abstract: More than 1 in 10 females (13%) reported being a victim of sexual assault in the 2012 Mortality, Morbidity, and Service Utilization Survey conducted in Haiti. This study aimed to describe the characteristics of sexual assault and its psychological consequences among female victims of sexual assault (patients) who presented to the Group for the Study of Kaposi's Sarcoma and Opportunistic Infections (GHESKIO) clinic in Port-au-Prince, Haiti, and determine which characteristics impact seeking medical evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Considering depressive symptoms, for example, female victims of sexual assault present a prevalence more than three times higher than other survivors. The few studies conducted among sexually assaulted women after the earthquake also showed that they present higher prevalence of traumatic consequences (Rahill et al ., 2015; Deschamps et al ., 2019). The results of the present study and previous research suggests that the consequences of enduring cumulative trauma can leave women more vulnerable to important traumatic consequences (Suliman et al ., 2009; Rahill et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering depressive symptoms, for example, female victims of sexual assault present a prevalence more than three times higher than other survivors. The few studies conducted among sexually assaulted women after the earthquake also showed that they present higher prevalence of traumatic consequences (Rahill et al ., 2015; Deschamps et al ., 2019). The results of the present study and previous research suggests that the consequences of enduring cumulative trauma can leave women more vulnerable to important traumatic consequences (Suliman et al ., 2009; Rahill et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The main issue in this case was the fact that women and girls lived in internally displaced persons camps, meaning they had no way to ensure their security, and this increased the probability of assault (Davis, 2010). However, traumatic consequences associated with sexual assault are poorly studied in Haiti (Cénat et al ., 2018; Deschamps et al ., 2019). The few studies that have been conducted have shown a significant association between sexual assault and mental health problems (Rahill et al ., 2015; Grelotti et al ., 2018; Deschamps et al ., 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately one in eight Haitian women aged 15 to 49 have had a lifetime experience of sexual violence (l' Enfance and Program, 2018). A majority of female survivors who present for care post-assault report significant physical and psychological trauma, including the lack of an emotional response to the trauma, fear, and flashbacks (Deschamps et al, 2019). However, socioeconomic and environmental factors make seeking care difficult, and women assaulted by an acquaintance as well as younger victims are more likely to delay medical treatment (Deschamps et al, 2019).…”
Section: Sexual Violencementioning
confidence: 99%
“…A majority of female survivors who present for care post-assault report significant physical and psychological trauma, including the lack of an emotional response to the trauma, fear, and flashbacks (Deschamps et al, 2019). However, socioeconomic and environmental factors make seeking care difficult, and women assaulted by an acquaintance as well as younger victims are more likely to delay medical treatment (Deschamps et al, 2019). While Haitian law recognizes rape as a criminal act, insidious forms of sexual violence such as sexual harassment and intimate partner violence are not currently recognized as criminal acts.…”
Section: Sexual Violencementioning
confidence: 99%